Comparison of Three, Five and Seven Levels Diode Clamped Multilevel Inverter Topologies based Shunt Hybrid Active Power Filter for Harmonics Compensation with Equal DC Link - Tugce Demirdelen; Mustafa Inci; Mehmet Tumay (International Journal of Applied Methods in Electronics and Computers, 2016)
The multilevel inverter is coming out as a new type of power inverter choice for high power applications. This type of inverter can constitute high voltage and decrease harmonics by its own circuit topology. This paper presents comparison of three, five and seven levels diode clamped multilevel inverter (DCMLI) topologies based shunt hybrid active power filter for harmonics mitigation of the nonlinear loads. The compensation process is based on synchronous reference frame method. Theoretical analyses and simulation results are obtained from an actual industrial network model in PSCAD. The simulation results are presented for a proposed system in order to demonstrate that the harmonic compensation performance meets the IEEE-519 standard.